Investigation of Factors Affecting the Number of Automobiles Owned by Households: Count Data Model - Kübranur Çebi Karaaslan (Istanbul Business Research)
The automobile industry is a service-oriented industry that is constantly developing. Households are the most important interlocutors in this industry. The study's aim in this direction is to determine what factors influence the number of automobiles owned by households. The factors that affect this number, as well as the extent of these affects, have been investigated in the study. The study's data set was obtained from the Turkish Statistical Institute's Household Budget Surveys. Count data models were used in the study. As a result of the study, the gender, age, educational status, marital status, working status of the household head, household size, annual available income, second house ownership, saving status, eating out habits, going to the movie habits, going to the market habits, difficulty in accessing public transportation services, difficulty in accessing compulsory education services and the variables of the survey year were statistically significant. The information presented in this study is expected to help decision makers and policymakers who benefit from the automobile sector, particularly automobile industry manufacturers.